Alternative Paradise - 21st Century Museum of Contemporary Art, Kanazawa (Kanazawa : 21st Century Museum of Contemporary Art Kanazawa, 2005)
Akiyama, Yoh ; Cardelus, Maggie ; Dagdelen, Canan ; Filomeno, Angelo ; Fukasawa, Naoto ; Hara, Kenya ; Iwai, Toshio ; Kanazawa, Kenichi ; Kitagawa, Hiroto ; Kuma, Kengo ; Murayama, Ruriko ; Nakamura, Tetsuya ; Saga, Atsushi ; Wilson, Anne ; Zezmer, Sofi
biog., ind. tent., gr. tent. p. 143-147
Engels, Japans
Exhibition "Alternative Paradise", 21st Century Museum of Contemporary Art Kanazawa, 05.11.2005 - 05.03.2006
boek